Aquatic adaptations in Mesoamerica : subsistence activities in ethnoarchaeological perspective - Williams, Eduardo, (Archaeopress pre-Columbian archaeology ;, 2022)
This text explores the subsistence strategies that ancient Mesoamericans implemented to survive and thrive in their environments. It discusses the natural settings, production sites, techniques, artifacts, cultural landscapes, traditional knowledge, and other features linked to human subsistence in aquatic environments.